2020
DOI: 10.1093/jisesa/ieaa140
|View full text |Cite
|
Sign up to set email alerts
|

Mating Systems of the Tree-Killing Bark Beetle Polygraphus proximus (Coleoptera: Curculionidae: Scolytinae)

Abstract: Polygraphus proximus Blandford (Coleoptera: Curculionidae: Scolytinae) has caused mass mortality of fir (Abies spp. (Pinaceae)) forests across large areas of Russia in the past decade. More recently, mass mortality of A. veitchii  Lindl. due to P. proximus infestation has been reported in Japan. This bark beetle species traditionally has been considered to be polygynous because their galleries have multiple gallery arms, and because harem-polygyny is common in the tribe Polygraphini. Although the mating system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Whereas it is expected that sex and/aggregation pheromones exist, these were never confirmed (Kabe, 1959;Nobuchi, 1980). The mating system of P. proximus is monogyny (Kerchev, 2014a;Köbayashi & Takagi, 2020), and the females produce double-armed horizontal mother-galleries beneath the bark in which they lay their eggs (Kabe, 1959;Nobuchi, 1966;Kerchev, 2014a;Köbayashi et al 2022). Each adult offspring makes its own exit hole (Kabe, 1959;Nobuchi, 1980).…”
Section: Bark Beetlesmentioning
confidence: 99%
“…Whereas it is expected that sex and/aggregation pheromones exist, these were never confirmed (Kabe, 1959;Nobuchi, 1980). The mating system of P. proximus is monogyny (Kerchev, 2014a;Köbayashi & Takagi, 2020), and the females produce double-armed horizontal mother-galleries beneath the bark in which they lay their eggs (Kabe, 1959;Nobuchi, 1966;Kerchev, 2014a;Köbayashi et al 2022). Each adult offspring makes its own exit hole (Kabe, 1959;Nobuchi, 1980).…”
Section: Bark Beetlesmentioning
confidence: 99%
“…Other studies have indicated that the males produce a pheromone which attracts females (Kerchev 2014b) or that both males and females of P. proximus can secrete aggregation pheromones (Krivets et al 2019). P. proximus is a monogamous species, unlike most other species in the Polygraphus genus (Kerchev 2014b;Köbayashi and Takagi 2020). In four other Polygraphus species, male-specific aggregation pheromones have been found.…”
Section: Chemoecologymentioning
confidence: 92%
“…The mating system of P . proximus is monogynous (Kerchev, 2014a ; Köbayashi & Takagi, 2020 ). Although a male sex pheromone is suspected to play a role in mating, this role has not been confirmed yet (Kabe, 1959 ; Nobuchi, 1980 ).…”
Section: Introductionmentioning
confidence: 99%
“…The emergence period and subsequent flight of the first generation of adults occur at the end of spring or at the beginning of summer (May-July), and the second generation emerges from the infested trees at the end of summer (August-September;EFSA, 2020;EPPO, 2014). The mating system of P. proximus is monogynous (Kerchev, 2014a;Köbayashi & Takagi, 2020). Although a male sex pheromone is suspected to play a role in mating, this role has not been confirmed yet (Kabe, 1959;Nobuchi, 1980).…”
mentioning
confidence: 99%